2023
DOI: 10.1186/s13046-022-02588-8
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: LncRNA BCAR4 promotes migration, invasion, and chemo-resistance by inhibiting miR-644a in breast cancer

Abstract: Background Metastasis and drug resistance of breast cancer have become a barrier to treating patients successfully. Long noncoding RNAs (lncRNAs) are known as vital players in cancer development and progression.  Methods The RT-qPCR were used to detect the gene expression. Colony formation assay, would healing assay, and transwell assay were performed to investigate oncogenic functions of cells. CCK8 assay was used to detect the cell viability. Wes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…For example, continual overexpression of HOTAIR can affect the degree of chromatin openness of tumor cells, thereby regulating gene expression and ultimately promoting the metastasis of breast tumors to the lung in mice [28] . lncRNA BCAR4 accelerates cell migration and infiltration through the miR-644a/CCR7 axis and the MAPK pathway and upregulates ABCB1 to induce chemoresistance in BC [29] . The mechanism of action of lncRNAs is primarily based on their different cellular localizations.…”
Section: Discussionmentioning
confidence: 99%
“…For example, continual overexpression of HOTAIR can affect the degree of chromatin openness of tumor cells, thereby regulating gene expression and ultimately promoting the metastasis of breast tumors to the lung in mice [28] . lncRNA BCAR4 accelerates cell migration and infiltration through the miR-644a/CCR7 axis and the MAPK pathway and upregulates ABCB1 to induce chemoresistance in BC [29] . The mechanism of action of lncRNAs is primarily based on their different cellular localizations.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are abnormally expressed in various types of cancers, and differentially expressed lncRNAs in plasma or serum have become an emerging focus area in noninvasive diagnostic applications [23], including intrahepatic cholangiocarcinoma [27], gallbladder carcinoma [28], glioblastoma [29], and prostate carcinoma [30]. Although the functions and molecular mechanisms of most lncRNAs are still unknown, increasing evidence has shown that lncRNAs may play important roles in the occurrence, progression, and metastasis of tumors [31,32]. Recently, an increasing number of lncRNAs have been found to be related to the prognosis of PaCa.…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is one of the most common malignant tumors that threaten women's health, and with the socioeconomic development and increasing life pressure, breast cancer patients tend to be younger. [1][2][3] Breast cancer in young women is characterized by late stage, high histological grade, high invasiveness, lymphatic vessel emboli, and bone marrow metastasis, compared with Western countries, its mortality and morbidity are increasing year by year. [4][5][6] Young women with breast cancer face more psychological problems, such as anxiety about a higher risk of recurrence, stress about marriage, childbirth, and work, negative emotions such as anxiety and depression often occur in different degrees during treatment, which lead to the decline of quality of life, immune function, poor treatment compliance, and aggravate the adverse reactions of treatment, etc., therefore, it is of great significance to pay attention to the research of negative emotion psychological intervention in young patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%